Building a transgenic sexing strain for genetic control of the Australian sheep blow fly Lucilia cuprina using two lethal effectors - Ying Yan (BMC Genetics, 2020)
Abstract Background The sterile insect technique (SIT) has been successfully used in many pest management programs worldwide. Some SIT programs release both sexes due to the lack of genetic sexing strains or efficient sex separation methods but sterile females are ineffective control agents. Transgenic sexing strains (TSS) using the tetracycline-off control system have been developed in a variety of insect pests, from which females die by either of two commonly used lethal effectors: overexpression of the transcription factor tetracycline transactivator (tTA) or ectopic expression of a proapoptotic gene, such as head involution defective (hid). The lethality from tTA overexpression is thought to be due to “transcriptional squelching”, while hid causes lethality by induction of apoptosis. This study aims to create and characterize a TSS of Lucilia cuprina, which is a major pest of sheep, by combining both lethal effectors in a single transgenic strain. Results Here a stable TSS of L. cuprina (DH6) that carries two lethal effectors was successfully generated, by crossing FL3#2 which carries a female-specific tTA overexpression cassette, with EF1#12 which carries a tTA-regulated Lshid Ala2 cassette. Females with one copy of the FL3#2 transgene are viable but up to 99.8% of homozygous females die at the pupal stage when raised on diet that lacks tetracycline. Additionally, the female lethality of FL3#2 was partially repressed by supplying tetracycline to the parental generation. With an additional Lshid Ala2 effector, the female lethality of DH6 is 100% dominant and cannot be repressed by maternal tetracycline. DH6 females die at the late-larval stage. Several fitness parameters important for mass rearing such as hatching rate, adult emergence and sex ratio were comparable to those of the wild type strain. Conclusions Compared to the parental FL3#2 strain, the DH6 strain shows stronger female lethality and lethality occurs at an earlier stage of development. The combination of two tTA-dependent lethal effectors could improve strain stability under mass rearing and could reduce the risk of resistance in the field if fertile males are released. Our approach could be easily adapted for other pest species for an efficient, safe and sustainable genetic control program.